Current Knowledge of Endolysosomal and Autophagy Defects in Hereditary Spastic Paraplegia - Toupenet Marchesi, Liriopé (Cells, 2021)
Hereditary spastic paraplegia (HSP) refers to a group of neurological disorders involving the degeneration of motor neurons. Due to their clinical and genetic heterogeneity, finding common effective therapeutics is difficult. Therefore, a better understanding of the common pathological mechanisms is necessary. The role of several HSP genes/proteins is linked to the endolysosomal and autophagic pathways, suggesting a functional convergence. Furthermore, impairment of these pathways is particularly interesting since it has been linked to other neurodegenerative diseases, which would suggest that the nervous system is particularly sensitive to the disruption of the endolysosomal and autophagic systems. In this review, we will summarize the involvement of HSP proteins in the endolysosomal and autophagic pathways in order to clarify their functioning and decipher some of the pathological mechanisms leading to HSP.